Revision of the Eurybrachidae (XVII). The new Australian genus Kamabrachys gen. nov. with ten new species (Hemiptera: Fulgoromorpha) - Constant, Jérôme (European Journal of Taxonomy, 2023)
The Australian genus of Eurybrachidae (Hemiptera, Fulgoromorpha) Kamabrachys gen. nov. is described to accommodate Platybrachys signata Distant, 1892 and Euronotobrachys plana Kirkaldy, 1906, the former being the type species. The new combinations Kamabrachys signata (Distant, 1892) gen. et comb. nov. and K. plana (Kirkaldy, 1906) gen. et comb. nov. are subsequently proposed. Ten new species are also included in the genus and described: K. andersoni gen. et sp. nov., K. brennani gen. et sp. nov., K. campbelli gen. et sp. nov., K. danielsi gen. et sp. nov., K. falcata gen. et sp. nov., K. fasciata gen. et sp. nov., K. pedemontana gen. et sp. nov., K. rieki gen. et sp. nov., K. v-carinatum gen. et sp. nov. and K. waineri gen. et sp. nov. The male and female genitalia of each species are illustrated and photographs of habitus, distribution maps, biological data and an identification key are provided. The mating behaviour of K. signata is described, illustrated and discussed. The genus Kamabrachys currently contains 12 species and is associated to trees in the family Myrtaceae.